Physical and Mechanical Properties of Plantation - Grown Acacia leucophloea, A. Nilotica and A. Tortilis from Mohindergarh (Haryana) - Shukla, N. K.; Verma, P. C.; Lal, Krishan; Lal, Mohan; Sanyal, S. N. (Indian Forester, 1990)
Based on the tests conducted on small clear specimens of plantation grown Acacia leucophloea. A. nilolica and A. tortilis from Mohindergarh (Haryona), their physical and mechanical properties have been reported and discussed. Although all the three species are heavier than Teak, they are not superior to Teak in several mechanical properties. Based on suitability indices, these species have been grouped as very heavy and moderately steady timbers. From strength point of view, all the three species are suitable for constructional purposes, railway sleepers, tool bandies, fence posts, agricultural implements, anvil blocks, mallet heads etc. A. nilotica and A. tortilis are also suitable for the manufaCture of dunnage pallets.